The Influence of Product Completeness and Goods Arrangement on Repurchase Interest at Indomaret Tanjung Jambu Muara Enim - Sri Setiati; Darwin Kesuma; Mujari Mujari (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine how product completeness and merchandise layout partially and simultaneously influence repurchase intention at Indomaret Tanjung Jambu Muara Enim. The sample size for this study was 84 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation. The results of this study indicate a significant partial effect of product completeness on repurchase intention at Indomaret Tanjung Jambu Muara Enim, and a significant partial effect of merchandise layout on repurchase intention at Indomaret Tanjung Jambu Muara Enim. The F-test indicates that product completeness and merchandise layout simultaneously influence repurchase intention at Indomaret Tanjung Jambu Muara Enim.